Continuous reproduction under a bimodal precipitation regime in a high elevation anole (Anolis mariarum) from Antioquia, Colombia (2011)
ABSTRACT: Reproductive activity was studied in two populations of Anolis mariarum during rainy and dry season months in the Antioquia department of Colombia. Minimum size at maturity was comparable at the two sites for both males (37-39 mm SVL) and females (44 mm SVL). At the population level, reproduction was continuous, with the majority of adult males and females reproductively active even during the dry season months. Juvenile size distributions also were uniform across seasons, consistent with the conclusion that recruitment is not pulsed in these populations. However, there was some evidence that certain females may lower their reproductive rates during the dry season, especially at the site receiving the least total annual precipitation (1700 mm). These results further support accumulating evidence that populations of Anolisspecies inhabiting the climatic equator region, where the annual precipitation regime is bimodal, are capable of maintaining continuous reproduction even when annual precipitation amounts are relatively low. In contrast, Anolis populations in areas receiving comparable amounts of annual precipitation during a single rainy season tend to cease reproductive activity during the longer dry season each year.